ANALISIS PENGENDALIAN PERSEDIAAN SUKU CADANG PESAWAT B737-NG DENGAN PENDEKATAN MODEL PERIODIC REVIEW DI PT. X - Ahyadi, Harwan; Khodijah, Siti (Bina Teknika, 2017)
PT. X is one of the companies engaged in the field of an aircraft-maintenance and repairing services. PT. X classifies the aircraft spare parts into three groups namely rotable, repairable, and expandable. PT. X has a problem of having shortage inventory of the expandable spare part with 9 unit total of shortage in 2016. If this problem occurs continuously, it can increase the total inventory cost. Therefore, this study discusses the improvement of the inventory control of the expandable spare parts.The first phase of this study is forecasting the existing spare parts of the A Classes. Then, we determine the maximum inventory and the average inventory in warehouse using min-max method. After that, we determine the inventory level which covers ordering period (T), maximum inventory (R) and the average inventory in warehouse using Periodic Review Models. The final phase of this study is comparing the total inventory cost between Periodic Review Models and Min-Max method.The Classification with ABC method result 5 spare parts from A Class with a percentage of total items are 12.5% from 40 total item. Meanwhile, the total value of A Class amounted to 71.80% that had Rp 132,285,644.22 from the total price Rp 184,218,274.36. Periodic Review Models result an ordering period (T) and maximum inventory (R) which is optimal and can minimizes shortage 0 unit from 6 unit in A Class. With this decreased of shortage, it can minimizes the total inventory cost from the company. The comparative results between the total inventory cost using Periodic Review Models and Min-Max Method is Periodic Review Models has a smaller total inventory cost than Min-max Method with a total saving of inventory cost amounted Rp 81,121,836.62 and the percentage savings of 39.25%.